Testosterone-loaded GM1 micelles targeted to the intracellular androgen receptor for the specific induction of genomic androgen signaling - Peinetti, Nahuel (2020)
Androgens play a central role in homeostatic and pathological processes of the prostate gland. At the cellular level, testosterone activates both the genomic signaling pathway, through the intracellular androgen receptor (AR), and membrane-initiated androgen signaling (MIAS), by plasma membrane receptors. We have previously shown that the activation of MIAS induces uncontrolled proliferation and fails to stimulate the beneficial immunomodulatory effects of testosterone in prostatic cells, becoming necessary to investigate if genomic signaling mediates homeostatic effects of testosterone. However, the lack of specific modulators for genomic androgen signaling has delayed the understanding of this mechanism. In this article, we demonstrate that monosialoganglioside (GM1) micelles are capable of delivering testosterone into the cytoplasm to specifically activate genomic signaling. Stimulation with testosterone-loaded GM1 micelles led to the activation of androgen response element (ARE)-regulated genes in vitro as well as to the recovery of normal prostate size and histology after castration in mice. In addition, these micelles avoided MIAS, as demonstrated by the absence of rapid signaling pathway activation and the inability to induce uncontrolled cell proliferation. In conclusion, our results validate a novel tool for the specific activation of genomic androgen signaling and demonstrate the importance of selective pathway activation in androgen-mediated proliferation.